1987
DOI: 10.1073/pnas.84.14.5048
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein purified from a human lung cancer cell line.

Abstract: A protein with biological activities similar to parathyroid hormone (PTH) has been purified from serum-free culture medium obtained from a human lung cancer cell line (BEN). A major protein band of 18 kDa was obtained on NaDodSO4/polyacrylamide gels, with faint bands at 35 kDa and 67 kDa. Biological activity was associated only with the 18-kDa band. Amino acid sequence analysis of the material purified by HPLC revealed that 8 of the 16 residues were identical with those of human PTH. Antibody raised to a corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
228
0
9

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 671 publications
(241 citation statements)
references
References 26 publications
4
228
0
9
Order By: Relevance
“…Parathyroid hormone-related protein (PTHrP) was dis covered in 1987 in humans as the circulating peptide responsible for the syndrome of humoral hypercalcemia of malignancy (HHM; Moseley et al, 1987). PTHrP and parathyroid hormone (PTH), the main hypercalcemic hor mone in vertebrates, evolved from a common, ancestral gene.…”
Section: Pthrp Its Discoverymentioning
confidence: 99%
“…Parathyroid hormone-related protein (PTHrP) was dis covered in 1987 in humans as the circulating peptide responsible for the syndrome of humoral hypercalcemia of malignancy (HHM; Moseley et al, 1987). PTHrP and parathyroid hormone (PTH), the main hypercalcemic hor mone in vertebrates, evolved from a common, ancestral gene.…”
Section: Pthrp Its Discoverymentioning
confidence: 99%
“…Parathyroid hormone-related protein was first identified as the mediating factor responsible for hypercalcemia associated with certain human malignant tumors (humoral hypercalcemia of malignancy, HHM), (Moseley et al, 1987). Immunodetectable PTHrP is present in a variety of tumors, especially those of squamous cell origin (Danks et al, 1989); however, it is also found in a range of normal cells, particularly human keratinocytes (Danks et al, 1989).…”
mentioning
confidence: 99%
“…Furthermore, by using rabbit anti-mid-region PTHrP, we specifically revealed a single band of approximately 7 kDa related to the mid-region, as described for other tumors. (9)(10)(11)(23)(24)(25) We also measured RNA levels of both PTHrP and PTH-R1 (Fig. 1D) in selected plasma cell samples, based on the highest cytometric expression.…”
Section: Calcium and Pthrp Serum Levelsmentioning
confidence: 99%
“…(7,8) PTHrP has been primarily reported in patients with osteotropic malignancies, such as breast, lung, and renal cancers, who show skeletal disease and hypercalcemia. (9)(10)(11)(12) Subsequent studies have described its functional effects through either paracrine or autocrine cell stimulation by tumors with no skeleton involvement and even by several normal tissues. (13)(14)(15) An intracrine effect of PTHrP has been also postulated in breast cancer to improve the nucleocytoplasmic trafficking that accelerates cell cycle progression, RNA transcription, and transport.…”
Section: Introductionmentioning
confidence: 99%